1996
DOI: 10.1111/j.1432-1033.1996.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of the Neutral Protease Vimelysin from Vibrio Sp. T1800

Abstract: The kinetics of the hydrolysis of dipeptide and tripeptide substrates by the recently discovered neutral protca\e from Vihrio species T1800 (vimelysin) were studied. In the pH dependence of the apparent second-order rate constant, the pK,, value of vimelysin (~6 . 5 ) was significantly lower than thermolysin (8.3 1. although the pK,, (~5 . 1 ) values were comparable (5.0). The kJKn,,,i,,,l parameter for hydrolysis of Fua-Gly-PheNH2 (Fua = furylacryloyl) was more than sevenfold greater than for Fua-Gly-LeuNH,. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(37 reference statements)
3
11
0
Order By: Relevance
“…T1800 discovered by K. Oda et al in 1996, is a unique enzyme characterized by its high activity at low temperature and its resistance to organic solvents [1][2][3][4]. Recently, we cloned and sequenced a gene encoding vimelysin (ORF: 1821 bp) [5].…”
Section: Introductionmentioning
confidence: 99%
“…T1800 discovered by K. Oda et al in 1996, is a unique enzyme characterized by its high activity at low temperature and its resistance to organic solvents [1][2][3][4]. Recently, we cloned and sequenced a gene encoding vimelysin (ORF: 1821 bp) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of an impressive amount of sequence, structural, and kinetic data renders this group of proteases an ideal subject for rational design strategies. Although some of the family members have been characterized individually (5,(21)(22)(23)(24), a consistent comparison with an identical substrate set and a uniform set of assay conditions has never been conducted. Previously it was suggested that TLPs exhibit a preference for large hydrophobic P 1 Ј residues (Leu or Phe) (1,17,21,22).…”
mentioning
confidence: 99%
“…There are several LBP in the intestine [13, 29, 30, 31, 32], but L-FABP is unlikely to play a major role, as suggested by the marked decline in jejunal L-FABP mRNA, but no alteration in lipid uptake (table 5). Recent support for the uncoupling between intestinal lipid uptake and LBP comes from the findings that (1) clones of mice with a disrupted gene for the intestinal FABP (I-FABP) are viable, have elevated plasma triacylglycerol, and weigh more than the wild-type littermates [56], and (2) dietary and diabetic alterations in lipid uptake are not paralleled by similar alterations in LBP expression [57].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we did not measure BBM lipids, so we are not able to comment upon whether the absence of an effect of steroids on fatty acid uptake was due to their lack of effect on BBM lipids or on the protein-mediated components of uptake [29, 30, 31, 38, 55]. There are several LBP in the intestine [13, 29, 30, 31, 32], but L-FABP is unlikely to play a major role, as suggested by the marked decline in jejunal L-FABP mRNA, but no alteration in lipid uptake (table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation